Utilization of Digital Marketing & Content Creator for Promotion of Entrepreneurship: Pemanfaatan Digital Marketing & Content Creator untuk Promosi Kewirausahaan - Lusia Putri, Siska; Lucy Chairoel; Tri Rachmat Riski; Febri Rahadi; Nabila Safira; M. Siddiq Partiti; Nuzulya Iqwa Suriani (Journal of Community Service and Application of Science, 2024)
Technological developments, the use of smartphones and internet access provide innovation in marketing activities. Entrepreneurs have new strategies in marketing the goods they produce which were originally marketed offline and can then be marketed online. Online marketing is one of the digital marketing strategies. Digital marketing activities are an important point in entrepreneurship promotion activities, considering that all forms of activity, especially in the business sector, have gone through the digitalization stage, so understanding in the digital marketing process must be improved so that they are not left behind and goals can continue to be achieved. The use of digital marketing is needed to improve the entrepreneurial marketing skills of students at SMA 7 Padang, SMK 4 Padang, and SMA 3 Tebo, so that students can implement digital marketing and be able to increase their business potential. Digital marketing involves starting from content creation, placing online advertisements, website optimization, email marketing, relations with online media, to becoming a social media admin. One application of digital marketing in business is content creation. This activity provides guidance regarding digital marketing strategies using content creation methods via social media platforms.